2022
DOI: 10.1155/2022/9978167
|View full text |Cite|
|
Sign up to set email alerts
|

Application and Research of Computer Intelligent Technology in Modern Agricultural Machinery Equipment

Abstract: Every country, including China, is deeply concerned and interested in the topic of agricultural machinery automation. The world’s population is growing at an astronomical rate, and as a result, the need of food is also growing at an astronomical rate. Farmers are forced to apply more toxic pesticides since traditional methods are not up to the task of meeting the rising demand. This has a major impact on agricultural practices, and in the long run, the land becomes barren and unproductive. Intelligent technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Sensors have the capability to gather information pertaining to various environmental factors such as temperature, humidity, light exposure, acidity level, among others. The timely detection of any form of contamination or abnormality is crucial for the implementation of appropriate intervention measures such as in the works done by (Yang et al, [25]; Kim et al, [26]; Ramli et al, [27]).…”
Section: The Internet Of Things (Iot) System For Fscmentioning
confidence: 99%
“…Sensors have the capability to gather information pertaining to various environmental factors such as temperature, humidity, light exposure, acidity level, among others. The timely detection of any form of contamination or abnormality is crucial for the implementation of appropriate intervention measures such as in the works done by (Yang et al, [25]; Kim et al, [26]; Ramli et al, [27]).…”
Section: The Internet Of Things (Iot) System For Fscmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%